2019
DOI: 10.1016/j.nbd.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine nucleus: An integrative view with implications on Deep Brain Stimulation

Abstract: The pedunculopontine nucleus (PPN) is a reticular nucleus located in the mesencephalic and upper pontine tegmentum. Initially, characterized by its predominant cholinergic projection neurons, it was associated with the "mesencephalic locomotor region" and "reticular activating system". Furthermore, based on histopathological studies, the PPN was hypothesized to play a role in the manifestation of symptoms in movement disorders such as Parkinson's disease (PD). Since axial symptoms represent unmet needs of PD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 172 publications
(238 reference statements)
1
27
0
Order By: Relevance
“…The clinical effects of STN-DBS has been suggested to result from modulations of the connectivity within the cortico-striato-thalamo-cortical loop 44 and of basal ganglia circuits that also affect sleep physiology 45 . Furthermore, the pedunculopontine nucleus and globus pallidus externa are both connected to STN [46][47][48] and are important in sleep regulation. Studies have shown that DBS in these areas increases REM sleep 46,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effects of STN-DBS has been suggested to result from modulations of the connectivity within the cortico-striato-thalamo-cortical loop 44 and of basal ganglia circuits that also affect sleep physiology 45 . Furthermore, the pedunculopontine nucleus and globus pallidus externa are both connected to STN [46][47][48] and are important in sleep regulation. Studies have shown that DBS in these areas increases REM sleep 46,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The PPN plays an important role in balance function, as it is an important part of MLR and has a close relationship with balance function [10,11]. Some scholars have shown that stimulation of the PPN can alter motor behavior [12].…”
Section: Plos Onementioning
confidence: 99%
“…DBS is the standard of surgical care for Parkinson’s Disease (PD) where electrodes are chronically implanted into the subthalamic nucleus and often extending into the mesencephalic substantia nigra [ 27 , 28 ]. The pedunculopontine nucleus is another brainstem target being evaluated for implanted neuromodulation systems to improve postural and gait instability in PD [ 29 ]. It is important to note that DBS and IMT are starkly different in neurological indication, operational parameters and hardware design.…”
Section: Discussionmentioning
confidence: 99%